Digit Ratio (2D:4D) and its relation to Mental Rotation performance and Creativity as a Mating Display - Bould, Anne M (My University, 2008)
The digit ratio (2D:4D) between the length of the index finger (2D) and the ring finger (4D) has been proposed as a negative correlate of levels of prenatal testosterone in humans. The present study investigated the relationship between 2D:4D, mental rotation performance and the use of creativity as a mating display after viewing pictures of sexy women. The study aimed to reproduce the finding of a negative correlation between 2D:4D and mental rotation performance. It also aimed to reproduce the finding that the presence of mating cues can increase the level of creativity shown by men. It then aimed to link this increase in creativity to 2D:4D. 74 males had their right-hand 2D:4D measured from photocopies and were timed whilst completing a mental rotation task. Participants were shown a painting and asked to write a short story in 3 minutes. Half of the participants were asked to rate 6 pictures of sexy women and the other half rated 6 pictures of cars. All participants were then asked to write another short story in 3 minutes. All stories were rated for creativity by a panel of 4 judges. No relationship was found between 2D:4D and mental rotation performance. A trend was observed for creativity to be greater in the second story written but no effect of mating cues on creativity was observed. 2D:4D was not found to be related to creativity. An effect was shown for longer stories to be rated as more creative. The present study concludes that 2D:4D is not related to mental rotation performance or creativity. Creativity in men is not affected by the presence of mating cues.
Keywords: 2D:4D; Creativity; Mental Rotation; Mating Display